Efficacy of Ranolazine in Patients With Symptomatic Hypertrophic Cardiomyopathy: The RESTYLE-HCM Randomized, Double-Blind, Placebo-Controlled Study. (January 2018) - Olivotto, Iacopo; Camici, Paolo G.; Merlini, Piera Angelica; Rapezzi, Claudio; Patten, Monica; Climent, Vicent; Sinagra, Gianfranco; Tomberli, Benedetta; Marin, Francisco; Ehlermann, Philipp; Maier, Lars S.; Fornaro, Alessandra; et al.
Abstract : Background: The late sodium current inhibitor ranolazine reverses the main electrophysiological and mechanical abnormalities of human hypertrophic cardiomyopathy (HCM) cardiomyocytes in vitro, suggesting potential clinical benefit. We aimed to assess the effect of ranolazine on functional capacity, symptomatic status, diastolic function, and arrhythmias in HCM. Methods and Results: In this multicenter, double-blind, phase 2 study, 80 adult patients with nonobstructive HCM (age 53±14 years, 34 women) were randomly assigned to placebo (n=40) or ranolazine 1000 mg bid (n=40) for 5 months. The primary end point was change in peak VO2 compared with baseline using cardiopulmonary exercise test. Echocardiographic lateral and septal E/E′ ratio, prohormone brain natriuretic peptide levels, 24-hour Holter arrhythmic profile, and quality of life were assessed. Ranolazine was safe and well tolerated. Overall, there was no significant difference in VO2 peak change at 5 months in the ranolazine versus placebo group (delta 0.15±3.96 versus −0.02±4.25 mL/kg per minute; P =0.832). Ranolazine treatment was associated with a reduction in 24-hour burden of premature ventricular complexes compared with placebo (>50% reduction versus baseline in 61% versus 31%, respectively; P =0.042). However, changes in prohormone brain natriuretic peptide levels did not differ in the ranolazine compared with the placebo group (geometric mean median [interquartile range], −3 pg/mL [−107, 142 pg/mL] versus 78 pg/mL [−71, 242 pg/mL]; P =0.251). Furthermore, E/E′ ratio and quality of life scores showed no significant difference. Conclusions: In patients with nonobstructive HCM, ranolazine showed no overall effect on exercise performance, plasma prohormone brain natriuretic peptide levels, diastolic function, or quality of life. The drug showed an excellent safety profile and was associated with reduced premature ventricular complex burden. Late sodium current inhibition does not seem to improve functional capacity in HCM. Clinical Trial Registration: URL:https://www.clinicaltrialsregister.eu . Unique identifier: 2011-004507-20 Abstract : Supplemental Digital Content is available in the text.